State in society : studying how states and societies transform and constitute one another - Migdal, Joel S. (Cambridge studies in comparative politics., 2001)
"The essays in this book trace the development of Joel S. Migdal's "state-in-society" approach. His process-oriented analysis illuminates how power is exercised around the world, and how and when patterns of power change."--Jacket